Global differences in the prevalence of the CpG island methylator phenotype of colorectal cancer - Advani, Shailesh Mahesh; Advani, Pragati Shailesh; Brown, Derek W; DeSantis, Stacia M; Korphaisarn, Krittiya; VonVille, Helena M; Bressler, Jan; Lopez, David S; Davis, Jennifer S; Daniel, Carrie R; Sarshekeh, Amir Mehrvarz; Braithwaite, Dejana; et al. (BMC cancer, 2019)
BACKGROUND: CpG Island Methylator Phenotype (CIMP) is an epigenetic phenotype in CRC characterized by hypermethylation of CpG islands in promoter regions of tumor suppressor genes, leading to their transcriptional silencing and loss of function. While the prevalence of CRC differs across geographical regions, no studies have compared prevalence of CIMP-High phenotype across regions. The purpose of this project was to compare the prevalence of CIMP across geographical regions after adjusting for variations in methodologies to measure CIMP in a meta-analysis. METHODS: We searched PubMed, Medline, and Embase for articles focusing on CIMP published from 2000 to 2018. Two reviewers independently identified 111 articles to be included in final meta-analysis. We classified methods used to quantify CIMP into 4 categories: a) Classical (MINT marker) Panel group b) Weisenberg-Ogino (W-O) group c) Human Methylation Arrays group and d) Miscellaneous group. We compared the prevalence of CIMP across geographical regions after correcting for methodological variations using meta-regression techniques. RESULTS: The pooled prevalence of CIMP-High across all studies was 22% (95% confidence interval:21-24%; I2 = 94.75%). Pooled prevalence of CIMP-H across Asia, Australia, Europe, North America and South America was 22, 21, 21, 27 and 25%, respectively. Meta-regression analysis identified no significant differences in the prevalence of CIMP-H across geographical regions after correction for methodological variations. In exploratory analysis, we observed variations in CIMP-H prevalence across countries. CONCLUSION: Although no differences were found for CIMP-H prevalence across countries, further studies are needed to compare the influence of demographic, lifestyle and environmental factors in relation to the prevalence of CIMP across geographical regions.
Keywords: prevalence; Colorectal; Promoter Regions, Genetic; Geographic; lidé; Methylation; Humans; promotorové oblasti (genetika); Epigenetics; India; Publication Bias; pití alkoholu; Czech Republic; genetická heterogenita; kohortové studie; metylace DNA; Colorectal Neoplasms; Phenotype; CIMP; CpG ostrůvky; rizikové faktory; fenotyp; kolorektální nádory; DNA Methylation; Prevalence; umlčování genů; Česká republika; Cohort Studies; Indie; Gene Silencing; Alcohol Drinking; Genetic Heterogeneity; publikační zkreslení; Risk Factors; CpG Islands